The Influence of School Inspection to Quality Teaching/Learning of Children in Primary Schools - Mutabaruka, Fredrick; Kazooba, Charles Tushabomwe; Kemeza, Imelda (Advances in Social Sciences Research Journal, 2018)
The study assessed the influence of school Inspection towards quality teaching/learning in Primary Schools. The study had an overall population of 140 respondents selected from ten (10) schools and out of the 140 respondents targeted in the 10 schools, a sample size of only 103 respondents was investigated. Questionnaires were used as the main data collection tool. According to the study findings the geographical locations of some schools, limited resources to do inspection, tight schedule of duties by inspectors, weather conditions and other barriers that included embezzlement of funds meant for inspection, late central government remittances were the main barriers to school inspection. The study concluded that Inspectors of schools play an important role of ensuring that learners are prepared, presented, evaluated and have self-motivation. The study recommended that the working relationship between the team is characterised by regular formal and informal meetings to discuss progress in relation to achievement of outcomes with those carrying out inspection. Government needs to increase the budget allocated to school inspection such that the activity can be carried out as the work plans in the education department.